The Microsurgical Relationships between Internal Carotid-Posterior Communicating Artery Aneurysms and the Skull Base - Matsuo, Satoshi; Komune, Noritaka; Tsuchimochi, Ryosuke; Kai, Yasutoshi; Matsumoto, Kenichi; Haga, Sei; Inoue, Takuya (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective This study aimed to review the anatomical and clinical characteristics of internal carotid-posterior communicating artery (IC-PC) aneurysms, especially those located close to the skull base.Methods The microsurgical anatomy around the posterior communicating artery (PComA) was examined in a dry skull and five formalin-fixed human cadaveric heads. The clinical characteristics of 37 patients with 39 IC-PC aneurysms, who were treated microsurgically between April 2008 and July 2016, were retrospectively reviewed.Results The anterior clinoid process (ACP), as well as the anterior petroclinoidal dural fold (APF), which forms part of the oculomotor triangle, are closely related to the origin of the PComA. Among the 39 IC-PC aneurysms, anterior clinoidectomy was performed on 4 (10.3%) and a partial resection of the APF was performed on 2 (5.1%). Both of these aneurysms projected inferior to the tentorium, or at least part of the aneurysm's dome was inferior to the tentorium.Conclusion Proximally located IC-PC aneurysms have an especially close relationship with the ACP and APF. We should be familiar with the anatomical relationship between IC-PC aneurysms and the structures of the skull base to avoid hazardous complications.
Keywords: anterior clinoid process; anterior petroclinoidal dural fold; internal carotid artery; posterior communicating artery; skull base